Reducing the air temperature inside the simple structure greenhouse using roof angle variation - Krit Tashoo; Pichai Namprakai; Ratanachai Pairintra; Sirichai Thepa (Journal of Agricultural Sciences)
There is a problem with the natural ventilation of a Simple Structure Greenhouse (SSG), having a roof with a gable end and a roof vent placed at a height of <2.5 m above the greenhouse column, with an average roof angle of <15°, that causes the air temperature inside the greenhouse to be much higher than the ambient temperature (an average of 6-8 K), which can be found in greenhouses that are covered by plastic film. This investigation considers the flow pattern and temperature distribution in an empty greenhouse with a dimension of 48 m2 by using the computational fluid dynamic technique, CFD, as a tool for the study. It was found that the heat convection generated wake flows under the canopy by thermally driven ventilation, and that the heat was transferred from the moving air into the greenhouse by convection and was allowed through the hot temperature outlet via the sidewall vents by the wind. The change of the various roof angles at an average angle of 15°, 30° and 42° pitch, in combination with an external wind speed of <2.0 m s-1 , serves the purpose of reducing the temperature inside the greenhouse to approximately ambient air temperature, considering the loads of external wind speed applied to the roof. The investigation results of the ventilation rate and the wind pressure coefficient, at a reference roof angle of 30°, is adequate for greenhouse construction. There will be air ventilation, called mixed convection, inside the greenhouse where the Gr Re-2 <1 and temperature differences (Ti – To) at 2.5 m above ground are less than 2 K.